IDENTIFIKASI SEBARAN INTRUSI AIR LAUT WILAYAH MANGGAR BARU BALIKPAPAN TIMUR - Pratikno, Fathony Akbar; Prabowo, Iwan; Jamaluddin, Jamaluddin (PETROGAS: Journal of Energy and Technology, 2024)
The resistivity geoelectric method is very suitable for determining the condition of the earth's subsurface by studying the properties of the electric current contained in a rock. Seawater intrusion can occur naturally to a certain degree in most coastal aquifers, due to the hydraulic relationship between groundwater and seawater. This study was conducted by collecting subsurface data by measuring the resistivity value of the rock. In addition, surface observations were made directly by observing the condition of the groundwater level in the wells of the community in coastal areas. This study is directed at providing recommendations for the use of clean water for everyday life. Based on the resistivity value of the modeling results, it can be seen that seawater has intruded the research area. This is indicated by the very small resistivity value (0.168-0.469 Ωm) shown in the deep blue area in the modelings, and the depth of 3-9 meters below the earth surface. Keywords: aquifer, resistivity, seawater intrusion, Manggar Baru,